THE CONTRIBUTION OF THE TELAGA PUNGGUR FISHING PORT FOR FISHERIES SECTOR IN BATAM CITY KEPULAUAN RIAU PROVINCE - Setiarbi, Bayu; Zain, Jonny; Sari, T. Ersti Yulika (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
A series survey activities was conducted on October 18 th – 30th , 2015 at Telaga Punggur fishing port, Batam. The purpose of this study is to obtain data and information about contribution of Telaga Punggur fishing port on fisheries sector in Batam. By using survey method, the result showed that the contribution of fishing port in fisheries sector was shown number of fishing boat were 46.78% - 52.94%, number of fishing gear were 44,20 % - 47,16%, number of fisherman were 49.36% - 51.51%, number of fish catches were 51.63% - 55.59% and number of fish production were 56.27% - 58.70%.Keywords : Contribution, Telaga Punggur Fishing Port, Fishery Sector, Facilities, Services